TINGKAT KEPUASAN KONSUMEN TERHADAP PEMBELIAN MAKANAN PRODUK AYAM BAKAR ABMJ MELALUI E-COMMERCE GOJEK DI KOTA BANDAR LAMPUNG - Rahmasanti, Destia; Indriani, Yaktiworo; Sayekti, Wuryaningsih Dwi (Lampung University, 2021)
This research aims to determine the consumers’ characteristics, the stages of decision making, and consumers satisfaction on buying ABMJ grilled chicken through Gojek e-commerce in Bandar Lampung. The location was determined purposively, in which samples were 65 people. The data were analyzed using descriptive analysis method, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The research showed that the consumers who bought ABMJ through Gofood were mainly single women around 19-24 years old, had bachelor degree, and had monthly income around IDR2,600,000.00-IDR3,500,000.00. The consumer's decision making process was conducted through the introduction of needs, information search, alternative evaluation, purchase decision, and post-purchase evaluation. Ease of purchase encouraged consumers to make transaction through Gofood and consumed ABMJ grilled chicken for their meals. Consumers acquired the resources and information by their friends who had consumed ABMJ grilled chicken. Price and advertisement in Gofood feature was highly considered by consumers. The consumers made purchases depending on the circumstances, so there was no planning before and more than three purchases made in the last three months. Consumers were satisfied and would still buy even if the price of the ABMJ grilled chicken increases. The value of CSI was 79.22 percent; it showed that the customers had been completely satisfied. Based on the IPA analysis, customers valued that information clarity, photographic clarity, delivery time, and the safety of maintaining confidentiality of consumer’s identity should be improved.Key words: CSI, IPA, purchasing decision, satisfaction